Estudo dos efeitos comportamentais do extrato hidroalcoólico de folhas de Passiflora coccínea Aubl. - Guarnieri, Jaqueline Rigotti Kubiszeski (2019)
Popularly, the species of the genus Passiflora have been used as an anxiolytic, sedative, and against insomnia. Numerous bioactive substances are found in the leaves of Passiflora species, some of which have antioxidant activities such as polyphenols and between them stand out flavonoids. Evidence indicates analgesic activity, anxiolytic, neuroprotective, anti- inflammatory and antidepressant leaf extracts, fruits and stems of plants of this kind. The Passiflora coccinea is an abundant ornamental plant in the Amazon region and known as passion fruit bush or passionflower, this plant is rich in bioactive substances such as flavonoids, yet its biological activity, especially concerning anxiolytic and antidepressant activity was not elucidated. This study aimed to develop an integrative review gathering the available literature on the use of the genus Passiflora plants and evaluate the behavioral effects of Passiflora coccinea extract in mice through the Wide Field tests, Maze in Cruz High, Swim Forced and Hide spheres P. Coccinea. The sheets were collected, separated stem, dried and pulverized to obtain the extract. Initially, the plant material was moistened with a hydro alcoholic solution and then went through a cooking process for 15 minutes and macerate for 7 days, filtered and remaked. The resulting extract was dried to eliminate the solvent. The phytochemical screening was performed by the laboratory of pharmacognosy UFTM - Sinop. Swis Male mice were treated for 7 days with three doses of hydroalcoholic extract of P. coccinea (100, 200 and 300 mg / kg), Imipramine, and Diazepam. The animals were divided into groups (n = 10) treated and subjected behavioral tasks open, the plus-maze, hide ball test and forced swim test. Data were analyzed using Kruskal Wallis test and post hoc Dun. The integrative review showed anxiolytic and antidepressant therapy ability of plants of the genus Passiflora on primary animal studies. The phytochemical screening revealed a concentration of SAE 468.33. g-1 (gallic acid equivalent), confirming the presence of phenolic compounds elucidated by thin-layer chromatography on flavonoids and tannins. The results showed that acute treatment with the extract of P.